Investigating the induction of polyphenol biosynthesis in the cultured Cycolocarya paliurus cells and the stimulatory mechanism of co-induction with 5-aminolevulinic acid and salicylic acid - Ling, Li-Juan; Wang, Meng; Pan, Chuan-Qing; Tang, Dao-Bang; Yuan, En; Zhang, Yuan-Yuan; Chen, Ji-Guang; Peng, Da-Yong; Yin, Zhong-Ping (Frontiers in Bioengineering and Biotechnology, 2023)
Plant cell culture technology is an effective way to produce polyphenols, however, this way is still trapped in the dilemma of low content and yield. In the present paper, five elicitors including 5-aminolevulinic acid (5-ALA), salicylic acid (SA), methyl jasmonate (MeJA), sodium nitroprusside (SNP) and Rhizopus Oryzae Elicitor (ROE) were used to increase the content and yield of polyphenols in the cultured Cyclocarya paliurus (C. paliurus) cells. The results indicated that 5-ALA and SA showed better promotion effect on the polyphenol biosynthesis among the above-mentioned five elicitors, and the co-induction of these two elicitors displayed a synergistic effect. Under the co-induction of 50 μM 5-ALA and SA, the content and yield of total polyphenols of the cultured cells reached 8.0 mg/g and 147.12 mg/L, respectively, and especially the yields of cyanidin-3-O-galactoside, procyanidin B1 and catechin reached 28.83, 4.33 and 2.88 times that of the control group, respectively. Stimulation mechanism was interpreted by integrating transcriptome and metabolome analysis. It was found that expressions of TFs such as CpERF105, CpMYB10 and CpWRKY28 increased significantly, while CpMYB44 and CpTGA2 decreased. These great changes might further make the expression of CpF3´H (flavonoid 3'-monooxygenase), CpFLS (flavonol synthase), CpLAR (leucoanthocyanidin reductase), CpANS (anthocyanidin synthase) and Cp4CL (4-coumarate coenzyme A ligase) increase while CpANR (anthocyanidin reductase) and CpF3'5'H (flavonoid 3', 5'-hydroxylase) reduce, ultimately enhancing the polyphenols accumulation.